Microscopic Polyangiitis, Revisiting ANCA-Associated Vasculitis: Case Report and Review - Jiménez-López, Carlos E.; García-Mata, Fiama N.; Flores-Cervantes, Jonadab Z.; Manriquez-Vázquez, Domingo A.; Parra-Mora, Hector A.; Godinez-Muñoz, Luis E.; Valle-Rodríguez, Elliot; Antulio A. Silva-Sarno; David Martínez-Galla; Mariscal-Diaz, Oriana Y. (International Journal of Medical Science and Clinical Research Studies, 2025)
Microscopic polyangiitis (MPA) is a systemic autoimmune necrotizing vasculitis belonging to the group of antineutrophil cytoplasmatic antibody (ANCA)-associated vasculitis (AAV). Characterized by pauci-inmune crescentic glomerulonephritis without systemic involvement. AAV is an uncommon disease with an incidence of about 20 per million population per year in Europe and North America. The kidney is involved in more than 90% of MPA cases. Rapidly progressive glomerulonephritis is the most common clinical presentation or renal vasculitis, revealed by rapid deterioration of renal function, low-grade glomerular proteinuria, and constant microhematuria, with the presence of red blood cell casts in the urine sediment. Renal biopsy is the gold standard diagnostic test that confirms renal involvement of AAV. This report presents a case of a 23-year-old female with no pathologic history of any chronic disease, presented with acute kidney failure symptoms. Initial evaluation suggested rapidly progressive glomerulonephritis, but further diagnostic workup, including renal biopsy and auto-inmune serology confirmed MPA. The patient was treated with glucocorticoids and Mycophenolate mofetil. Significant improvement was observed, with complete resolution and normal kidney function at the 3-month follow-up.